Communicating compassionately: how the University of Exeter is changing the way it speaks with its students and why - Stoker, Ciaran; Cole, Jo (Perspectives: Policy and Practice in Higher Education, 2025)
The Compassionate Communications project at the University of Exeter is changing the way in which student-facing staff across the institution communicate with our student body. At the heart of this work is a focus on ensuring we as a university are inclusive, accessible, and supportive in the way in which we provide information to our increasingly diverse learners. Embedded within a wider strategy for improving student mental health and well-being across the institution, the project aims to complement existing work improving students' sense of belonging through the implementation of key principles and staff training. In addition, the project seeks to improve our use of terminology and the readability of student-facing policies and procedures across our digital landscape. The fundamental principle is recognition that good communications are central to improving the student experience; particularly in regard to a sense of belonging, safety, and understanding.